Ideology and Translation Studies in Present-Day China - Tang, Jun (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis essay examines the ideological dimension of translation studies in present-day China, which can be viewed as an indicator of any discernible change in ideological fluctuations of translation. Based on an overview of translation studies in present-day China, this essay argues that the most urgent problem is the domestic climate for the social, cultural, political, and institutional sub-systems of Chinese society. It is inadvisable to take the traditional cultural heritage or Western influences as the excuse or panacea for current problems in China. Local knowledge can be trivialized if cut off from the global setting, and the global setting becomes meaningless if local knowledge is ignored.